Effect of Atmospheric Pressure on Performance of AEA and Air Entraining Concrete - Yan Shi; Huaquan Yang; Shihua Zhou; Aiguo Wang; Xingdong Lv (Advances in Materials Science and Engineering)
The effect of atmospheric pressure on performance of air entraining agent (AEA) and air entraining concrete was studied in Tibet and Hubei, China. The result shows that the reduced atmospheric pressure increased surface tension and lowered foaming property of solution. The AEA with excellent foaming ability and stability is preferred in low atmospheric pressure. The freeze-thaw deterioration process of hardened pastes is relatively faster under low atmospheric pressure. The effect of air pressure on concrete frost resistance performance is more sensitive than the mechanical property. The bigger pores and poor uniformity of internal pore size distribution led to the deterioration of concrete macroscopic properties. Therefore, the AEA varieties should be preferred, the dosage of AEA should be increased, and pore structure of pastes should be optimized to ensure the durability of concrete frost resistance for construction in low-pressure areas.